2010
DOI: 10.1007/s00421-010-1416-8
|View full text |Cite
|
Sign up to set email alerts
|

The influence of interval versus continuous exercise on thermoregulation, torso hemodynamics, and finger dexterity in the cold

Abstract: The purpose of this study was to evaluate how interval (INT) and continuous (CONT) exercise alter body temperatures and manual dexterity in the cold (5 degrees C). Fourteen young men underwent two trials consisting of a 90-min period of acute cold exposure (ACE), 30 min of exercise (INT or CONT), and a 60-min recovery period (REC). Participants donned approximately 1 clo but the hands remained bare for the entire protocol so that a steep decline in dexterity performance occurred prior to the initiation of exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 61 publications
1
25
0
Order By: Relevance
“…Exercise has also been shown to improve dexterity. Muller et al (168) reported that working at 50% VO 2peak for 30 min performed in the middle of a 5 • C coldair exposure increased dexterity by ∼25%, although it did not approach the baseline levels that were measured in a temperate environment. In contrast, cold habituation, either through natural exposure or laboratory cold-water immersions, has not been shown to improve manual dexterity (114,169).…”
Section: Manual Dexteritymentioning
confidence: 93%
“…Exercise has also been shown to improve dexterity. Muller et al (168) reported that working at 50% VO 2peak for 30 min performed in the middle of a 5 • C coldair exposure increased dexterity by ∼25%, although it did not approach the baseline levels that were measured in a temperate environment. In contrast, cold habituation, either through natural exposure or laboratory cold-water immersions, has not been shown to improve manual dexterity (114,169).…”
Section: Manual Dexteritymentioning
confidence: 93%
“…The CPT is a widely used laboratory stimulus that increases sympathetic outflow to skeletal muscle (32,70) and increases myocardial oxygen demand (45,48). From a practical standpoint, people exposed to cold ambient conditions also experience hand pain (52) and reduced manual dexterity (53), thereby increasing their risk for accident (19). Thus physiological and perceptual responses to hand cooling have clinical and occupational applications.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were immediately excluded if they reported cardiovascular or metabolic disease or were taking any medications. They were of average aerobic fitness (44.7 ± 5 mL/kg/min) and body fatness (14.5 ± 4.9%) as determined via VO 2 peak test (cycle ergometry) and seven-site skinfold (mean = 153 ± 55 mm), respectively (Muller et al 2010). The protocol was approved by the Kent State University Institutional Review Board and all volunteers gave signed informed consent.…”
Section: Subjectsmentioning
confidence: 99%
“…Similarly, it has been shown that moderate exercise (cycle ergometry) can improve finger dexterity following immobility in 5°C. When core and skin temperature increased, fine motor performance improved (Muller et al 2010). However, it is yet to be determined how the mode of exercise (interval vs. continuous, matched for energy expenditure) affects thermal sensation and hand pain.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation